Linguistic Narratives and the Construction of Social Values (A Study of Tāj al-ʿArūs Narratives as a Model) - Al-Mallouh, Dr. Hussein Fadhel Abbas Al-Mallouh; Mansour, Dr. Marwa Shakir Mansour (Sulaimani Journal for Humanities, 2026)
Language plays a fundamental role in shaping human thought, beginning with the moment of discovering metaphorical signifiers and culminating in the completion of phonetic signifiers. While the initial moment of assigning meaning to a signifier is metaphorical, this metaphor sheds its figurative cloak and dons objectivity, channeling thought toward knowledge production by codifying signifiers within a shared cultural framework. As a result, each linguistic signifier acquires a definitive meaning, assumes relational significance within the structure of a complete sentence, and thus contributes to constructing knowledge-bearing discourse that influences societal behavior through various forms of narration. Linguistic narratives determine the meaning of individual terms and reveal embedded ethical, epistemological, and religious structures. These narratives elevate language to a cognitive model that successive generations seek to recover within inherited traditions. The Arab heritage, in particular, is rich in narratives that carry moral, social, and religious dimensions. Considering the long-standing nature of linguistic inquiry through codification, and given that it served as the foundation for other knowledge domains such as Qur'anic exegesis and the study of rhetorical miracles, understanding language through its narratives becomes essential for uncovering how social systems are constructed and preserved. Tāj al-ʿArūs contains an immense wealth of narratives that define the meanings of words. These narratives are especially evident in the etymological roots and figurative meanings of terms, reflecting key moments in the construction of Arab culture. This opens the door to investigating the intellectual school behind these narratives—its management of knowledge, its employment of language as a tool for constructing meaning, and the subsequent effect of language on society. These linguistic narratives are thus perceived both as reflections of historical behavioral patterns and as frameworks that shape conduct according to inherited norms.
Keywords: Language; Narratives; Society; Culture; Tāj alʿArūs